Review of the levitation mass method a precision mechanical measurement method - Fujii, Yusaku; Jin, Tao; Mitatha, Somsak; Yupapin, Preecha P.; Hou, Wenmei; Yamaguchi, Takao (My University, 2011)
This paper firstly has a brief review of the present status and future prospects of a method for precision mechanical based on the levitation mass method (LMM). The LMM has been proposed and improved by the author. The force generated by the actuator is measured as the inertial force of the mass levitated with sufficiently small friction using an aerostatic linear bearing and connected to the moving part of the actuator. During the measurement, the Doppler shift frequency of the laser beam reflected by the mass is measured with a high accuracy with the help of an optical interferometer. Subsequently, the velocity, position, acceleration, and inertial force of the mass are calculated using based on this frequency. Simultaneously, the current and voltage supplied to the actuator are measured.
Keywords: Dynamic force correction; Impact force; Inertial force; Inertial mass; Levitation Mass Method; Optical interferometer